Understanding Concepts and Causes of Student Misconceptions on Work and Energy - Rahmadhani, Rahmadhani (PILLAR OF PHYSICS EDUCATION, 2025)
Misconceptions among students refer to misunderstandings they hold regarding learning concepts that differ from the scientific principles established by experts. This study aims to analyze students' conceptual understanding and identify the causes of misconceptions related to the topics of work and energy. To achieve this, a survey research method was employed, utilizing a set of 15 multiple-choice questions rated on a five-point scale for data collection. The sample consisted of 80 students from three different schools. The findings revealed that 50% of the students experienced misconceptions regarding the law of conservation of energy. The sources of these misconceptions varied across the three schools and were primarily attributed to the textbooks used in lessons, explanations provided by the teachers, individual reasoning, and peer influence. Notably, a significant number of students exhibited misconceptions stemming from their own reasoning. Consequently, it is recommended that teachers identify and address these misunderstandings to help minimize the occurrence of misconceptions among students.